The Effect of Vehicle Traffic on Wildlife in Denali National Park - Burson III, S.L.; Belant, J.L.; Fortier, K.A.; Tomkiewicz III, W.C. (ARCTIC, 2000)
We recorded observations of caribou (Rangifer tarandus), grizzly bear (Ursus arctos), Dall sheep (Ovis dalli) and moose (Alces alces) along the Denali National Park and Preserve road corridor during 1995-97. We compared these observations to similar data from previous studies to evaluate the effect of an increase in traffic on the number of animals sighted and their behavior. Between 1972 and 1997, annual visitation to Denali National Park increased from about 45000 to 350000, with attendant increases in traffic on the park road. The mean number of caribou, grizzly bear, and Dall sheep observed did not decline (p > 0.301) from 1973 to 1997. The number of moose observed declined by more than 50% (R² = 0.529, p < 0.001). The estimated population of moose also declined over the same period (R² = 0.374, p = 0.002). The distance from the park road at which caribou and grizzly bears were sighted did not change (p > 0.787), but fewer moose (p < 0.031) were observed within 100 m of the road and fewer sheep (p < 0.011) were observed between 400 and 500 m from the road. Adverse behavioral responses to traffic (e.g., running from vehicles) occurred in less than 1.3% of observations for each species. Increased traffic on the park road apparently has not caused significant changes in abundance, distribution, or behavior of caribou, grizzly bear, Dall sheep, and moose in the park road corridor. De 1995 à 1997, on a rapporté des observations du caribou (Rangifer tarandus), du grizzli (Ursus arctos), du mouflon de Dall (Ovis dalli) et de l'orignal (Alces alces) dans le corridor routier de la réserve et du parc national Denali. On a comparé ces observations à des données similaires recueillies au cours d'études antérieures visant à évaluer l'impact d'une augmentation du trafic sur le nombre d'animaux aperçus et sur leur comportement. Entre1972 et 1997, le nombre annuel de visiteurs au parc national Denali est passé d'environ 45 000 à 350 000, ce qui a amené une augmentation de la circulation sur la route du ...